POLA ASUH OTORITER DENGAN ONLINE RESILIENCE PADA REMAJA AWAL - Wahyu Caraka Pratama; Doddy Hendro Wibowo (Jurnal Psikohumanika, 2023)
Adolescence nowadays considered as digital-natives where internet has become their part of their life especially in this pandemic. However, internet not always contains of positivity, but also negativity. Adolescence needs an ability to filter and response appropriately in internet world called online resilience. This research aim is to see the correlation between authoritarian parenting style and online resilience in early adolescence. Participants of this research is 243 students of a Middle School in Semarang Regency, Central Java with age ranged from 12-15 years old. This research used quantitative design. Data was collected by random sampling using authoritarian parenting style scale and online resilience scale. Data was analyzed using Pearson’s product-moment correlation with help of SPSS 21. The result of this research showing that there’s a negative correlation between authoritarian parenting style and online resilience r = -.188